Peningkatan Kinerja Guru Melalui Supervisi Edukatif Kolaboratif Secara Periodik - Tiurma Simbolon (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This research was motivated by the weak ability of teachers in understanding the curriculum, especially at SD Negeri 25 Rianiate, district. Samosir. This School Action Research was conducted at SD Negeri 25 Rianiate, Pangururan sub-district, Samosir district. Based on the findings of the research results, there are four things put forward in this action research, namely conclusions about: (1) Improving teacher performance in preparing lesson plans, (2) Improving teacher performance in implementing learning, (3) Improving teacher performance in assessing learning achievement, (4) Improved teacher performance in carrying out follow-up results of student achievement assessments. Keywords: collaborative; teacher performance; supervision  Abstak: Penelitian ini dilatarbelakangi lemahnya kemampuan guru dalam pemahaman kurikulum khususnya di SD Negeri 25 Rianiate, kab. Samosir. Penelitian Tindakan Sekolah  ini dilaksanakan di SD Negeri 25 Rianiate, kecamatan Pangururan, kabupaten Samosir. Berdasarkan temuan hasil penelitian ada empat hal yang dikemukakan dalam penelitian tindakan ini, yakni simpulan tentang: (1) Peningkatan kinerja guru dalam menyusun rencana pembelajaran, (2) Peningkatan kinerja guru dalam melaksanakan pembelajaran, (3) Peningkatan kinerja guru dalam menilai prestasi belajar, (4) Peningkatan kinerja guru dalam melaksanakan tindak lanjut hasil penilaian prestasi belajar siswa. Kata kunci: kolaboratif; kinerja guru; supervisi